REPRESENTASI GENERASI SANDWICH PADA FILM HOME SWEET LOAN SEMIOTIKA ROLAND BARTHES - Syaira Amanda Putri; Silvina Mayasari; Sari Ekowati Hadi (CV Edujavare Publishing, 2025)
This study examines the representation of the sandwich generation phenomenon in the film